Removal of arsenic from alkaline process waters of gold cyanidation by use of γ-Fe2O3@ZrO2 nanosorbents - Feng, C.; Aldrich, Chris; Eksteen, Jacques; Arrigan, Damien (Elsevier, 2017)
Arsenic is a problem in gold mining, as it can adversely affect operations and poses a health hazard. Although a number of technologies has been developed for its removal, none of them is effective under all conditions. Adsorption in particular, is a promising approach, but most methods have concentrated on the purification of water under neutral or acidic conditions. In gold mining and metallurgical processing waters, these adsorbents tend to be less effective. In this study, the removal of As(III) and As(V) from simulated mining process waters by use of composite nanoparticles is considered. The particles consisted of γ-Fe 2 O 3 cores coated with ZrO 2 . The maximum Langmuir adsorption capacities of As(III) and As(V) were 62.2 mg/g and 18.3 mg/g, respectively, at a pH of 9. In the alkaline process waters from a gold cyanide leaching plant, adsorption of 42.3 mg/g for As(III) and As(V) collectively, remained satisfactory, despite the presence of multiple competitive ions. Moreover, the particles retained their capacities well after multiple cycles of regeneration.